A The The Relationship Between Individual Character And The Grade Point Average (GPA) of D III Midwifery Students of Cianjur College of Health Sciences - Abdillah, Soffa; Rahmah, Hasni; Widayati, Elizabeth; Sofiati, Fia (Universitas Jenderal Achmad Yani Yogyakarta, 2024)
Background: Character formation is an integration of various aspects, namely heart, mind, body and feeling holistically. GPA is the only learning outcome in an education. Individual character can have an impact on the achievement of students' GPA.Objective: The purpose of the study was the relationship between individual character and the Cumulative Achievement Index of D III Midwifery students at the Cianjur Health Sciences College.Method: The study was conducted a Cross-sectional plan with chi-square. The population in this study were 42 D III Midwifery students at the Cianjur Health Sciences College, taken as total sampling.Results: The results showed that students who had positive characters were 57.1% and students who had negative characters were 42.9%. Students who got a GPA of 2.00-2.75 were 23.8%, those who got a GPA of 2.75-3.50 were 71.4% and those who got a GPA of 3.51-4.00 were 4.8%. The highest percentage is found in students who have positive characters with GPA achievements of 2.75-3.50 of 91.7%, the lowest percentage is found in students who have positive characters with GPA achievements of 3.51-4.00 of 8.3%.Conclusion: The results of the study indicate that there is a significant relationship between individual character and Cumulative Achievement Index